Study on the degradation of T-2 toxin in beer by glow discharge plasma - WANG Xiaobo; LIU Jiannan; ZHENG Lin; CHEN Bingbing; FENG Zejun; DENG Qi (Shipin yu jixie, 2024)
Objective: Exploring the optimal process for the degradation of T-2 toxin in beer by glow discharge plasma（GDP） and its impact on the physicochemical indicators of beer. Methods: Based on single-factor experiments, a response surface optimization experiment with four factors and three levels was conducted using the Box Behnken method to determine the optimal degradation conditions for T-2 toxin in beer. Results: When the discharge voltage was 570 V, the action time was 18 minutes, the discharge current was 99 mA, and initial concentration of T-2 toxin was 8.5 μg/mL. Under the control of these conditions, the degradation efficiency of the T-2 toxin was the highest （89.21%）. After GDP treatment, the physical and chemical indicators of beer were tested, and the results showed a significant decrease in beer foam retention （P<0.05）, while other indicators remained unchanged. Conclusion: The optimal degradation conditions of GDP obtained by the response surface optimization model are accurate and reliable, which can be used for the degradation of T-2 toxin in beer. GDP can affect the brewing ability of beer, but it will not have a significant impact on other indicators.